Concurrent object-oriented programming for distributed real-time systems - Katsumi Maruyama (Information sciences, 1996)
Concurrent object-oriented programming is becoming an important programming paradigm in real-time system implementations, because it can effectively integrate object-oriented programming, concurrent processing, and distributed processing. As run-time efficiency and program maintainability are strongly required in real-time systems, elaborated tuning is required both in application system design and in language design. This paper explains how concurrent processing and distributed processing can be incorporated into object-oriented programming without sacrificing efficiency, by means of a newly proposed concurrent object-oriented language “ACOOL.” An application program example is also shown.